Book Notes [54, Fall 2004] - Finkel, Alvin (Labour / Le Travail, 2004)
The article briefly reviews Doug Smith's "How to Tax a Billionaire: Project Loophole and the Campaign for Tax Fairness;" "The Resilient Outpost: Ecology, Economy, and Society in Rural Newfoundland," edited by Rosemary Ommer; Susan Sleeper-Smith's "Indian Women and French Men: Rethinking Cultural Encounter in the Western Great Lakes;" Mark Franko's "The Work of Dance: Labor, Movement, and Identity in the 1930s;" "Friends of the People: Uneasy Radicals in the Age of the Chartists," by Owen R. Ashton and Paul A. Pickering, ; Steve Wright's "Storming Heaven: Class Composition and Struggle in Italian Autonomist Marxism;" Wendy Z. Goldman's "Women at the Gates: Gender and Industry in Stalin's Russia;" Julie R. Watts's "Immigration Policy and the Challenge to Globalization: Unions and Employers in Unlikely Alliance;" Heidi Tinsman's "Partners in Conflict: The Politics of Gender, Sexuality, and Labor in the Chilean Agrarian Reform, 1950-1973;" Rosa Isolde Reuque Paillalet's "When a Flower Is Reborn: The Life and Times of a Mapuche Feminist," edited and translated by Florencia E. Mallon; and S.A. Smith's "Like Cattle and Horses: Nationalism and Labor in Shanghai, 1895-1927."